2012
DOI: 10.1021/jp3055069
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Chemical, and Magnetic Investigations of Core–Shell Zinc Ferrite Nanoparticles

Abstract: We investigate here the internal structure of zinc ferrite nanoparticles designed and prepared by a soft chemistry method to elaborate magnetic nanocolloids. The strategy used to avoid acid dissolution modifies the chemical composition of the surface of the nanoparticles, which are described as a core of stoichiometric zinc ferrite surrounded by a maghemite shell. Measurements of X-ray absorption nearedge spectroscopy, extended X-ray absorption fine structure, and X-ray diffraction are undertaken to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 51 publications
(95 reference statements)
4
37
1
2
Order By: Relevance
“…The NPs size distribution was estimated by measuring the size of about 300 particles, using a log normal law of size distribution which corresponds to the probability density that a particle has a diameter d TEM = 7.1 nm, with a standard deviation σ TEM = 0.25. Figure 1b presents the normalized room temperature magnetization curve for NPs; the full line is the best fit of Langevin, adjusting the experimental data, which allowed us to determine m s = 172 kA/m, d mag = 6.8 nm and σ mag = 0.26. correlated to this mechanism of the core-shell model were reported in the works of Gomes et al [34], Figure 1 (a) presents the TEM picture of the sample and shows that the NPs are roughly spherical.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The NPs size distribution was estimated by measuring the size of about 300 particles, using a log normal law of size distribution which corresponds to the probability density that a particle has a diameter d TEM = 7.1 nm, with a standard deviation σ TEM = 0.25. Figure 1b presents the normalized room temperature magnetization curve for NPs; the full line is the best fit of Langevin, adjusting the experimental data, which allowed us to determine m s = 172 kA/m, d mag = 6.8 nm and σ mag = 0.26. correlated to this mechanism of the core-shell model were reported in the works of Gomes et al [34], Figure 1 (a) presents the TEM picture of the sample and shows that the NPs are roughly spherical.…”
Section: Resultssupporting
confidence: 74%
“…The calculation of the molar fraction is given by, χ m = [Mn]/([Mn] + [Fe]). Studies correlated to this mechanism of the core-shell model were reported in the works of Gomes et al [34], Martins et al [23], and Pilates et al [26]. Figure 1a presents the TEM picture of the sample and shows that the NPs are roughly spherical.…”
Section: Resultsmentioning
confidence: 66%
“…Even though the surface layer is not homogeneous and presents some remaining content of core divalent metals in the composition, the obtention of the core-shell structure by hydrothermal soft chemistry is remarkable. Indeed, our chemical core/shell approach well accounts for several structural and magnetic properties, such as coordination of core and shell metal ions 71 and intrinsic NPs' magnetization 63,72,73 . Figure 2b), the solid line represents the best magnetization fit calculated using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly due to the opportunity to combine at the very same time this technique specific to synchrotron radiation with other more classical spectroscopies such as Infrared [59,60], Raman [61,62], UV visible [63] spectroscopies or other techniques such as mass spectrometry with high time resolution [64]. Different breakthroughs have been also performed by combining XAS and X-Ray diffraction in heterogeneous catalysis [65][66][67][68][69][70][71][72][73][74][75][76][77] and more precisely on spinel [78]. Such approach allows the chemist to collect information on the catalytic reaction through the metal or the cations (through XAS) and through the molecules which interact at the surface of these nano-objects (through vibrational spectroscopies or through soft XAS [79]) at the very same time and on the very same catalyst.…”
Section: Introductionmentioning
confidence: 99%